THE EFFECT OF PRESSURE, OPPORTUNITY, AND RATIONALIZATION ON ACADEMIC FRAUD IN STUDENTS OF THE FACULTY OF ECONOMICS - Hartono; Adha, Maulana Amirul; Faslah, Roni (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The purpose of this study was to determine the effect of pressure, opportunity, and rationalization on academic fraud on students of the Faculty of Economics, Universitas Negeri Jakarta, class of 2019. This research is a quantitative study using the survey method and using multiple regression analysis. The sample in this study were 110 students using purposive sampling. The results of this study show: (1) There is a positive and significant effect of pressure on academic fraud in students of the Faculty of Economics, Universitas Negeri Jakarta, Class of 2019. (2) There is a positive and significant effect of opportunity on academic fraud in students of the Faculty of Economics, Universitas Negeri Jakarta, Class of 2019. (3) There is a positive and significant effect of rationalization on academic fraud in students of the Faculty of Economics, Universitas Negeri of Jakarta. (4) There is a positive and significant influence of pressure, opportunity, and rationalization on academic fraud in students of the Faculty of Economics, Universitas Negeri Jakarta, Class of 2019.